Assessing the use of External Grand Theories in Purchasing and Supply Management research. Issue 1 (March 2016) - Spina, Gianluca; Caniato, Federico; Luzzini, Davide; Ronchi, Stefano
Abstract: The paper examines the extant management literature on Purchasing and Supply Management (PSM) to assess the underpinning role of External Grand Theories (EGTs) – i.e., established theories drawn from other areas of economics, management and other social sciences. We perform an extensive and systematic literature review of 1055 papers in the 20 top management journals for the time period 2002–2010, bypassing a keyword search in favour of a complete scanning of a total of 14, 943 articles. Results show an analysis and classification of the most commonly used EGTs borrowed to underpin research on PSM. We also match research topics, methodologies and unit of analysis with EGTs. Finally, we investigate what is the nature of the research – exploratory, theory building and theory testing – supported by EGTs. Analyses find PSM to be poorly rooted in EGTs, which confirms PSM relatively lower theoretical maturity when compared with other disciplines. Transaction Cost Economics and the Resource Based View prove to be the most frequently adopted frameworks. Other theories emerge as interesting opportunities in combination with specific topics and methodologies. Highlights: We run an extensive and systematic literature review on Purchasing and Supply Management. We focus on the use of External Grand Theories in PSM research. We explore the use of EGTs in terms of research topics, methodologies, and unit of analysis. We explore the use of EGTs for different types of research (i.e., exploratory, theory testing, theory building).